EMPATI DAN PEMAAFAN PADA MAHASISWA FAKULTAS PSIKOLOGI UIN SUSKA RIAU - Lestari, Dwi Indra; Agung, Ivan Muhammad (Faculty of Ushuluddin and Humanities, 2016)
Forgiveness has one important in human interpersonal relation.The purpose of this study was to examine the relationship between empathy and forgiveness on undergraduate student. The participants undergraduate student were 309 (47: men, 262, women) from faculty of Psychology UIN Suska Riau. This research used two kinds of scale, empathy and forgiveness scale.The result showed: there is a significant and positive correlation between empathy and forgiveness.. The Implication of this result are discussed on the interpersonal relation contexts.